2000
DOI: 10.1142/s021798490000080x
|View full text |Cite
|
Sign up to set email alerts
|

ELECTROMECHANICAL COEFFICIENTS OF MAGNETOELECTRIC PZT–CoFe2O4 COMPOSITE

Abstract: The magnetoelectric property of composite materials consisting of piezoelectric and piezomagnetic constituents are of interest since the stresses induced in them on application of an external magnetic field are converted into electrical signals. The electrical output is primarily due to electromagnetic coupling between the two participating phases. The present paper deals with the evaluation of the electromechanical coupling in the magnetoelectric composite consisting of 50% lead zirconate titanate (Pb0.96Sr0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…An additional peak is clearly observed at 182°C at 1 MHz. This peak is similar to the kink occurred in the permittivity-temperature characteristics of pure PZT ceramics [7]. Figure 5 shows the ME coefficient at 1 kHz as a function of dc magnetic bias.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…An additional peak is clearly observed at 182°C at 1 MHz. This peak is similar to the kink occurred in the permittivity-temperature characteristics of pure PZT ceramics [7]. Figure 5 shows the ME coefficient at 1 kHz as a function of dc magnetic bias.…”
Section: Resultssupporting
confidence: 67%
“…4. The Curie temperature for PZT and CFO are 200 and 520°C [7], respectively. The Curie temperature of the sample 1250-1 is the same as that of PKI552 ceramic, viz.…”
Section: Resultsmentioning
confidence: 99%
“…Ryu et al [17], Cai et al [18] also observed this type of behavior in PZT+Terfenol-D, PZT+Terfenol-D+PZT laminated composites respectively. Srinivas et al [19] evaluated the electromechanical coupling coefficients in 50% PZT+50% CoFe 2 O 4 composites. As shown in the microstructure [14], the distribution of ferrite particles become more uniform and less connected when the amount of ferrite was low.…”
Section: Piezoelectric and Magnetoelectric Propertiesmentioning
confidence: 99%
“…The magnetic behaviour of ferrites depends on the number of parameters like cation distribution, site preference energies, covalency of bonds and the molecular field [26,27]. Theoretically, the ME output in the composites should increases with the ferrite content and it would be maximum for the composite with 50% ferrite and 50% ferroelectric provided that there is no depolarizing field [28].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Ryu et al [31], Cai et al [32] also observed this type of behaviour in PZT + Terfenol-D, PZT + Terfenol-D+ PZT laminated composites respectively. Srinivas et al [28] also evaluated the electromechanical coupling coefficients in 50% PZT + 50% CoFe 2 O 4 composites.…”
Section: Magnetoelectric Effectmentioning
confidence: 99%